2015
DOI: 10.1007/s11239-014-1166-2
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilic state in young patients with acute myocardial infarction

Abstract: The prevalence of thrombophilia and dyslipidemia among young survivors of acute coronary syndrome has not been clearly defined. The purpose of the current study was to investigate the prevalence of multiple markers of thrombophilia and dyslipidemia in a cohort of consecutive young survivors of acute coronary syndrome. The study cohort included 156 consecutive young patients (men <45 and women <50 years), admitted to the intensive cardiac care unit with newly diagnosed acute coronary syndrome. Analysis included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
9
0
4
Order By: Relevance
“…Previous investigations have reported that young ACS patients have a different risk factor profile compared with elderly ACS patients [ 7 , 22 24 ]. Hypertension is a known important risk factor for the development of coronary artery disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have reported that young ACS patients have a different risk factor profile compared with elderly ACS patients [ 7 , 22 24 ]. Hypertension is a known important risk factor for the development of coronary artery disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Multiple reports have also demonstrated the role of antiphospholipid antibody syndrome antibodies in accelerating the process of coronary atherosclerosis. 26 Hypertension Although a well-established risk factor, hypertension was less likely to be present in younger patients. 30 This observation is consistent with recent studies; however, consistent with angiographic data of coronary artery disease in the young showing a stronger predilection for single-vessel disease and in particular left main disease, hypertension is common in patients with left main coronary artery stenosis who are under the age of 45 years.…”
Section: Hypercoaguable Statesmentioning
confidence: 99%
“…При обследовании 156 молодых пациентов (мужчины <45 лет, женщины <50 лет) с ИМ E. Maor с соавт. выявили наличие, по крайней мере, одного лабора-торного показателя, соответствующего возможной тромбофилии в 47% случаев [38]. В популяции ИМбОКА наиболее часто выявляются резистентность фактора V Лейдена, а также дефицит активированного протеина C (у 12% и 3% пациентов, соответственно) [7].…”
Section: коронарный тромбоз/эмболияunclassified